2020
DOI: 10.1177/2325967120917919
|View full text |Cite
|
Sign up to set email alerts
|

The Femoral Head “Divot” Sign: A Useful Arthroscopic Sign of Hip Microinstability

Abstract: Background: A femoral head “divot” is a rare finding during hip arthroscopy. A linear chondral indentation can be observed on the femoral head, just lateral and parallel to the acetabular labrum. Purpose/Hypothesis: The purpose of this study was to describe a novel arthroscopic sign and retrospectively review patients with this finding. We hypothesized that this sign would be found in patients with characteristics consistent with hip microinstability. Study Design: Case series; Level of evidence, 4. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Both studies found that male sex was correlated with higher traction forces required for adequate hip distraction, thus increasing their risk of traction‐related injury. Similarly, prior investigations of hip microinstability have described majority female populations [12, 13, 20, 24]. Hormonal differences, particularly in serum relaxin concentrations, have been proposed as a cause of higher incidences of ligamentous laxity in female patients [8].…”
Section: Discussionmentioning
confidence: 94%
“…Both studies found that male sex was correlated with higher traction forces required for adequate hip distraction, thus increasing their risk of traction‐related injury. Similarly, prior investigations of hip microinstability have described majority female populations [12, 13, 20, 24]. Hormonal differences, particularly in serum relaxin concentrations, have been proposed as a cause of higher incidences of ligamentous laxity in female patients [8].…”
Section: Discussionmentioning
confidence: 94%
“…described a femoral head divot sign in 14 patients, identifying a linear chondral indentation on the femoral head just lateral and parallel to the acetabular labrum in patients identified to have hip microinstability. 10 They proposed that, in the setting of microinstability, this area may experience repetitive edge loading leading to the head deformation.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 8 Making the diagnosis of microinstability is based on a multitude of factors that are identified through a thorough history and physical exam, imaging studies, and intraoperative findings. 1 , 2 , 4 , 5 , 9 , 10 Moreover, the diagnosis of hip microinstability can occur with normal radiographs or be a concurrent diagnosis with labral injuries, femoroacetabular impingement (FAI), hip dysplasia or borderline dysplasia. Therefore, a high index of suspicion is necessary to make the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…113,114 Arthroscopic evaluation of the joint can show classical patterns of inside-out chondral wear of the acetabulum and central femoral head wear or the 'divot' sign. 115 In addition, fluoroscopic assessment of the hip joint to analyze the degree and ease of femoral head distraction can be informative. 110 Initial treatment involves activity modification, strengthening the surrounding hip musculature and core muscles through physiotherapy.…”
Section: Authors Year Journal Trial Name Level Of Evidence Outcomementioning
confidence: 99%